Experiences of Female Rugby Union Players and Practitioners in Rehabilitation Following a Shoulder Injury - Caroline Sarah White; Paul Garner; Ian Horsley; Andrew Soundy (Sports, 2025)
Background: Little is known about the perspectives of elite female rugby union players and practitioners towards rehabilitation and return to play (RTP) following shoulder injuries and how to manage these complex injuries. Methods: An interpretive hermeneutic phenomenology study was undertaken within a subtle realist paradigmatic view. Twenty semi-structured interviews were conducted with elite female rugby union players and practitioners working in elite female rugby union. Data were analysed using reflective thematic analysis. Results: Four themes emerged from the data: (1) growth of the women’s game, which involved several influences on the support and resources players received; (2) different viewpoints between players and practitioners concerning injury reporting and objective testing; (3) threats to identity, a player-only generated theme centred around the risk to their career following a significant injury and the isolation they faced; and (4) RTP, exploring strategies and influences to players’ and practitioners’ confidence in the RTP process following a shoulder injury. Conclusions: Practitioners should consider the non-physical factors during the rehabilitation process and the theory of care concept in supporting and collaborating with female rugby union players following a shoulder injury.